Детінізація економіки як основа фінансової безпеки держави - Бригінець Олександр Олексійович (Фінансове право, 2014)
У статті розглянуто процес впливу тіньової економіки на стан вітчизняної фінансової безпеки держави. Визначено особливості функціонування тіньового сектору економіки України. The paper deals with the role of a perfect definition of the impact of shadow economy on the life of society. It determines peculiarities of the domestic legislative support for fighting shadow economy. The paper is prepared with the use of legal acts which are in force and relate to this problem. The title of the paper: Unshadowing of economy as the basis of financial security of the state. It is noted that one of the key factors that negatively affect the condition of the financial security of the state is extensive manifestation of shadow economic acts. A lot of papers in domestic and foreign scientific literature are devoted to fighting shadow economy, but they mainly describe shadow economy as a national phenomenon, and it is not considered as a factor affecting the state of financial security. The aim of this paper is to determine the operation of the shadow sector of the national economy and the process of its unshadowing as a basis for the provision of financial security of the state. The paper determines the reasons which led to a significant spread of shadow relations in the economy of our state and the consequences to which it led. Some aspects of the unshadowing of the domestic economy are also considered. Besides, the paper analyses the Concept of reforming of the tax system of Ukraine, prepared by the Cabinet of Ministers of Ukraine and intends to implement a fundamentally new mechanism of tax administration. The author concludes that most of the changes that have occurred recently in the legislation in the sphere of implementation process of unshadowing of the economy as a threat to the domestic financial security of the state, there are only a declaration of intentions to fight the shadow economy. Our state, like others, seeks to minimize this phenomenon and its impact on financial security of the state